124 The Microsurgical Learning Curve: Can We Make the First Steps Faster and Safer; A Cadaveric Study with A Novel Principle of Learning. (12th October 2021) - Medjoub, K; Wielechowska, K; Harris, T; Curnier, A; Ahmed, J
Abstract: Aim: Learning anew surgical technique can be a daunting experience for both the teacher and learner. Raising free flaps is a complex process, and our aim is to find out whether using Hi-fidelity simulation on cadavers can make the learning faster and safer. Method: We used fresh frozen cadavers according to our local protocols. In the first stage of the study, we used 4 upper limbs in the first instance using different dye techniques. We use these in an international course and obtain feedback from the trainees. Results: To a novel learner, we found that using a bright green dye was the important factor in making the first steps of learning easier and faster. This is perhaps due to the confounding information when raising the flap. We found that it made understanding the concept of free flap raising much faster when clarified with colour. It also made anticipating the steps easier when identifying the perforators. To an experienced trainee/consultant: We found teaching the concept of perforators easier, the ease of finding the perforators would raise confidence of the novel trainees. They will be able to conceptualize the principles of flap raising much faster. They believed it would also make them quicker at anticipating steps of the procedure. Conclusions: Learning is an incredible process that we still have to better control and understand. Using simple tricks such as colour changes can make initial learning faster, which means cheaper and safer